Torah as Wisdom in 4 Ezra and 2 Baruch - Gore-Jones, Lydia 19XX- (Journal for the study of Judaism, 2021)
Abstract This essay is concerned with the meaning of torah and its relationship with wisdom in late Second Temple Judaism. It has been previously argued that, as the Mosaic torah had gained dominance, the wisdom school absorbed and accommodated the Mosaic torah tradition, and yet maintained all the essential elements of the sapiential tradition. Through a study of two Jewish apocalypses, 4 Ezra and 2 Baruch, the essay discovers not only the sapientialization of the Mosaic torah, but also the total submission of the wisdom tradition under the authority of the Mosaic torah tradition to gain legitimacy. It argues that this is done through a submission of sapiential revelations to the Mosaic revelation received at Sinai, and a portrayal of wisdom recipients and apocalyptic visionaries as types of Moses. This process reflects religious innovation under the disguise of compliance with established, older traditions.